Sleepless Plains : Fossilisation and Peasant Kinship in Scandinavia - Halberg, Simon (The Department of Arts and Cultural Sciences, Lund University, 2025)
What does it mean to live with fossil fuels? Studying farmers in the sugar beet districts on the plains of Southern Scandinavia, this thesis investigates the history and ethnography of a troubled relationship between subterranean energy and everyday life. How did it come about that farmers first came to depend on fossil fuels? What changes followed in their use of the land and their gendered division of labour? And in what ways does this history impact contemporary farmers in their views of what constitutes a pretty field? To answer these questions, this thesis proposes an ethnological theory of fossilisation as a total social fact. By doing so, the aim is to explore how fossilisation has shaped an agrarian mode of life and a way of thinking about what one can do with the landscape and with the kinship relations in it. Both landscape and kinship are studied ethnologically as structures which are continually transformed by changes in everyday life over the past 150 years. It is shown how feelings of shame about having weeds in the field and the disappearance of fallow land have historically been tied up with the fossilisation process. Similarly, the emergence of industrial agriculture on the plains testifies to a biographical and metabolic connection to the old sugar plantations in the West Indian colonies which, in complex ways, constituted the blueprint after which domestic agricultural modernity took shape. The impact on the daily lives of farming men and women, children and adults, landowners and the dispossessed is traced through the different waves of fossilisation, after which the current landscape finds itself to be both the victim and driver of a changing climate.
Date: 2025-12-12 Time: 13:15 Place: sal C126, LUX, Helgonavägen 3, Lund External reviewer Name: Lien, Marianne Title: professor Affiliation: Universitetet i Oslo
Keywords: Fossilisation; cultural landscapes; peasant kinship; steam ploughs; tractors; dehorsing; sugar beets; weed shame; myth of the green transition; ethnography; history; genealogy